Behavior Increase Body Immunity - Sri Mayasari Puspa (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Covid-19 has spread to several countries including Indonesia. Responding to the growing trend of spreading and contagion of Covid-19, which has continued to increase, since April 2020. The Covid-19 pandemic has become a disruption so we need to recognize, overcome, and prevent this uncertainty so that this uncertainty will end soon To provide advice to all levels of society to be alert to the Covid-19 outbreak as an effort to reduce the spread of the Covid-19 outbreak, one of which is to increase body immunity. The method used in this study is a survey method used to analyze the role of employees of Cibinong Sentra Medika Hospital in increasing body immunity. The survey results showed that the average "yes" answer was above 70% on the understanding and knowledge employees of Cibinong Sentra Medika Hospital about the Covid-19 virus and how to increase body immunity. The knowledge employees of Cibinong Sentra Medika Hospital about Covid 19 and community behavior regarding the prevention and transmission of Covid-19 is in a good category. This condition has become a good strength for employees of Cibinong Sentra Medika Hospital in the Covid-19 handling program. Efforts to prevent and monitor the spread of Covid-19 must continue to be carried out by various parties, in various locations/office environments or community associations/public places, including their respective communities/individuals so that there is no increase in the number of serious cases. The public is advised not to stress easily in the face of this uncertain situation during the Covid-19 pandemic